The Survival of Different Fungal Spores During Tabletting - A.Al-Shikli, Raghad; A.Abdul-Rasool, Alaa; M. Al-Hiti, Mustafa (Iraqi Journal of Pharmaceutical Sciences, 2017)
The survival of dried spores of A.flavus, Penicillia Spp., and Cladosporia Spp.inoculated into multivitamins and folic acid tablets were examined at different compression pressures.Survival of fungal spores decreased with increasing compression pressure. The level of survival at particular pressures was shown to depend on the size of the contaminating fungal spores.The lethal effect of tabletting was attributed to shearing forces upon the contaminating spores generated by interparticulate movement. This hypothesis was supported by the dependence of survival upon spore size. Key words: Fungal spores, microbial contamination.